Kepatuhan Pajak di Era Covid-19: Analisis Pengaruh Insentif, Sanksi, Pengetahuan, dan Pelayanan Pajak yang Dimoderasi oleh Sosialisasi Pajak - Permata, Shintya Dwi; Ravelby, Thesa Alif; Nisaa, Verselly (Jurnal Eksplorasi Akuntansi, 2025)
“The Covid-19 pandemic that hit Indonesia in early 2020 shifted the situation from a health crisis to an economic one, affecting national revenues, particularly from the tax sector. To sustain economic activity, the government issued various tax incentive policies, including Article 21/22/23/25 Income Tax and MSME Final Income Tax incentives, to encourage taxpayer compliance. However, compliance during the pandemic was also influenced by other factors such as tax sanctions, tax knowledge, services, and tax socialization. This study aims to examine the effects of tax incentives, sanctions, knowledge, and services on taxpayer compliance, with tax socialization as a moderating variable. This type of research is quantitative research. the population is taxpayers of Bengkulu province. The sampling technique used is purposive sampling with certain criteria with a sample of 200 respondents. The technique used to analyze the data using the Partial Least Square (PLS) method. The results show that tax incentives and services did not have a positive effect on compliance, while tax sanctions, tax knowledge, and tax socialization had significant positive effects. Moreover, tax socialization strengthened the influence of incentives and sanctions on compliance but did not moderate the effects of knowledge and services. The findings contribute theoretically by expanding understanding of compliance behavior during crises and practically by providing insights for policymakers to design more effective tax communication and education strategies.